Parents about School: from Factors Choice of Educational Institutions to the Real Information Children's School Life - K. Yu. Belousov (Дискурс)
Introduction. Large-scale reforms in the system of domestic school education in recent years have led to an increase in the importance of the role of parents as subjects of educational policy. The modern school, responding to the changes that have taken place in the interaction of the family and the educational institution, has begun to actively address research requests to parents in order to clarify their views on various aspects of the work of the school and the study of children. The purpose of the paper, therefore, is to illustrate examples of research requests from schools inSt Petersburg with a description of the factors of choosing an educational institution by parents, their awareness of various aspects of a child's life, assessing the size of the study load and student's attitude to school. The scientific novelty of the work is due to the content of the tools used, the peculiarities of constructing the sample used in data collection, as well as the duration of the study.Methodology and sources. The empirical basis of the study is the results of long-term surveys of parents of schoolchildren in grades 4, 9, 11 from 73 schools inSt Petersburg. Surveys were carried out between 2013 and 2019, according to the same methodology and tools for educational institutions. The total data set includes 4278 respondents. The selection of schools for the survey was carried out at random each year of the study. Correctional schools of various profiles were excluded from the sample.Results and discussion. The results of the study showed that the closeness of the school to home and a strong teaching staff are the most significant factors that play a decisive role in choosing a school, according to the parents’ opinion. Almost half of the respondents do not express their feelings about the size of the school load, considering it optimal. Only 10.8 % of parents consider the current school load to be excessively high. More than 20.0 % of parents do not have sufficient information about the child's relationship with teachers, the same number are poorly informed about his or her friends and acquaintances.Conclusion. With all the variety of problems that arise today in the relationship between the school and parents, the study nevertheless recorded a positive tone of parental responses, who  are  mostly  satisfied  with  the  choice  of school,  teachers,  the  existing psychological climate, etc. Parents who took part in surveys, revealing the point of view of students, they report that children go to school more often with interest and joy, they have many friends there, and in the family, they tell more good things about their educational institution than vice versa.